The Importance Of Distribution Channels To Increase Sales Of P&G Products In South Papua: Case Study Of Downy Fragrance Products At CV. Merauke Indah - Pawit Triyadi; Melinda Christanti Kwan (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
Distribution channels in a company play a very important role in ensuring that products or services produced by producers can reach final consumers efficiently and effectively. CV. Merauke Indah is one of the Sub Distributors located in Eastern Indonesia, namely in South Papua. The recommended alternative to overcome these obstacles is to increase accessibility to remote areas. Collaborate with local logistics service providers such as SIKI express expeditions. The efficiency in logistics management. Optimize delivery routes to determine the most efficient path based on road and weather conditions to be more efficient. Regular market surveys can also be carried out to understand consumer needs in various regions and adjust stock in the warehouse according to the survey results. Improving distribution channels is also an important part. CV. Merauke Indah is advised to use multimodal transportation that combines land, sea, and air routes to overcome infrastructure limitations. Building warehouses in strategic locations such as Boven Diguel Regency and Mappi Regency will also speed up distribution and reduce dependence on poor road conditions.